2020
DOI: 10.1016/j.cell.2020.09.020
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 Triggers Mitochondrial DNA Release via mPTP to Activate cGAS/STING in ALS

Abstract: Summary Cytoplasmic accumulation of TDP-43 is a disease hallmark for many cases of amyotrophic lateral sclerosis (ALS), associated with a neuroinflammatory cytokine profile related to upregulation of nuclear factor κB (NF-κB) and type I interferon (IFN) pathways. Here we show that this inflammation is driven by the cytoplasmic DNA sensor cyclic guanosine monophosphate (GMP)-AMP synthase (cGAS) when TDP-43 invades mitochondria and releases DNA via the permeability transition pore. Pharmacologic inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
509
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 618 publications
(524 citation statements)
references
References 62 publications
15
509
0
Order By: Relevance
“…Indirect evidence for this idea is supported by recent findings of transcriptional dysregulation in pathways involved in mitochondrial function and energy production in TDP-43-depleted motor neurons [17]. Moreover, TDP-43 has been shown to exert toxicity by entering mitochondria and specifically impairing OXPHOS complex I via the preferential binding of mitochondrially transcribed ND3/6 mRNAs and by inhibiting their translation to cause mitochondrial dysfunction and neuronal loss [107], as well as triggering mitochondrial DNA release and neuroinflammatory cGAS/STING activation [112]. Finally, recent work by Onesto et al showed that there is compensatory mitochondrial biogenesis, as evidenced by PGC1α upregulation, in dermal fibroblasts derived from patients with C9orf72-ALS [77].…”
Section: Discussionmentioning
confidence: 86%
“…Indirect evidence for this idea is supported by recent findings of transcriptional dysregulation in pathways involved in mitochondrial function and energy production in TDP-43-depleted motor neurons [17]. Moreover, TDP-43 has been shown to exert toxicity by entering mitochondria and specifically impairing OXPHOS complex I via the preferential binding of mitochondrially transcribed ND3/6 mRNAs and by inhibiting their translation to cause mitochondrial dysfunction and neuronal loss [107], as well as triggering mitochondrial DNA release and neuroinflammatory cGAS/STING activation [112]. Finally, recent work by Onesto et al showed that there is compensatory mitochondrial biogenesis, as evidenced by PGC1α upregulation, in dermal fibroblasts derived from patients with C9orf72-ALS [77].…”
Section: Discussionmentioning
confidence: 86%
“…Increased mRNA levels of Ccl5 and Cxcl10 was found to be cGAS dependent in both human and mouse striatal HD tissue further implicating the cGAS-STING pathway in driving the neuroinflammatory response in HD ( Sharma et al, 2020 ). A relationship between STING and TDP-43, a hallmark protein of ALS has recently been established with TDP-43 found to trigger mtDNA release into the cytoplasm, activating the cGAS-STING pathway ( Yu et al, 2020 ). Increased cGAS and cGAMP, the STING activating molecule produced by cGAS was detected in spinal cords and in the cortex of ALS mice overexpressing TDP-43 (Prp-TDP-43 Tg/+ ).…”
Section: Sting Activity In Chronic Cns Pathologiesmentioning
confidence: 99%
“…Increased cGAS and cGAMP, the STING activating molecule produced by cGAS was detected in spinal cords and in the cortex of ALS mice overexpressing TDP-43 (Prp-TDP-43 Tg/+ ). When STING was genetically deleted from these mice, the average lifespan increased by 40% and the mice exhibited improved rotarod performance compared to Prp-TDP-43 Tg/+ mice with intact STING ( Yu et al, 2020 ). Furthermore, elevated levels of the STING activator cGAMP were detected in spinal cord samples from ALS patients ( Yu et al, 2020 ).…”
Section: Sting Activity In Chronic Cns Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-selective MPTP may be permissive to DNA transport [ 124 , 125 ]. Translocation of mitochondrial DNA via MPTP was recently suggested in experiments with TDP-43-mediated inflammation; however, this suggestion was based largely on an effect of MPTP inhibitor cyclosporine A that was applied at a dose ~10 times higher than a specific dose [ 126 ]. An effect on an alternative target, calcineurin was also not ruled out.…”
Section: Mitochondrial Ros As Signaling Entities In Immunitymentioning
confidence: 99%